Implikasi Naskh Hadis Terhadap Status Ke-ḥujjah-annya - Lutfiyah, Lujeng (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2020)
No words were said in a vacuum. A hadith must be revealed because of certain conditions that are the cause, or certain things that are the goal. A condition or goal that is the cause of the disclosure of a hadith, can occur repeatedly from time to time. When there are changes in social conditions that cause changes in the statement (hadith) of the Prophet, then it does not necessarily indicate that the old statement is not used anymore, because the same conditions underlying the disclosure of the initial hadith may be repeated again. In understanding the Prophet's hadith it is very important to do contextualization. This is because the attitude of obedience and emulation of the Prophet is a command of Allah, and the hadith of the Prophet is also a primary guidance for Muslims. If the hadith of the Prophet is interpreted only literally all, then there will be many guidance that feels "obsolete", because it will not reach social change that cannot be avoided. Contextualization will make the hadith not insulated by the concept of ma‘mūl bih or ghayr ma‘mūl bih absolutely, especially with regard to the legal hadith undergoing the naskh process